INAPPROPRIATELY TREATED INTRACTABLE COUGH - Khattak, Muhammad Tahir (Journal of Ayub Medical College Abbottabad, 1992)
Chronic, non-productive cough has a variety of causes. In most cases the etiology is readily identifiable and treatable. Occasionally drugs induce a persistent cough which necessitates withdrawal of the offending agent. A case is presented in which drug- induced cough was misdiagnosed and inappropriately managed